Post-UNESCO Effect: Chhau’s journey from Cultural Sentiment to Commercialization - Chakraborty, Ayantika (Ethnographica et Folkloristica Carpathica, 2021)
Chhau, a traditional masked dance form of West Bengal has been enlisted as ‘UNESCO- Intangible Cultural Heritage of Humanity, 2010’. In 2015, UNESCO along with the MSME of Government of West Bengal developed a ‘Rural Craft Hub’ in Chorida village of Purulia district centring Chhau. Consequently, tourism in the area got international and national patronage. This entire phenomenon encouraged the commercialization of the traditional dance and craft form associated with Chhau as a result of heritagization. Unfortunately, the implication of the heritagization happened in a flawed fashion which eventually led to folklorization and institutionalization while compromising their contextual significance. The paper explores how heritagization ensures the sustainability of intangible tradition like Chhau while leading to folklorization and institutionalization of performance and craft. The paper also documents the history and ritualistic significance of Chhau to draw a lucid comparison between the traditional form and the form which is the result of folklorization. The paper establishes that the Heritagization- Folklorization- Institutionalisation are intertwined with each other in the context of Chhau. From the interviews of the tourists and locals associated with Chhau, it is evident that the organization concerned with policy making should keep it in mind that an enormous distortion of craft and performance comes along when the target buyers in the market are alien to the traditional context. In such a scenario, the contextual significance of a craft form can be kept intact if the targeted buyers can be made aware of the contextual and functional relevance of the folkloric element that they are consuming in its modernized version.